2008
DOI: 10.1002/jbm.a.31946
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of surface oxide layers on medical grade Ni‐Ti alloy during straining

Abstract: Medical grade Ni-Ti alloys with shape memory or pseudo-elastic behavior exhibit good biocompatibility because of an electrochemically passive oxide layer on the surface. In this work, the mechanical stability of surface oxide layers is investigated during reversible pseudo-elastic deformation of commonly applied medical grade Ni-Ti wires. Surface oxide layers with varying thickness were generated by varying annealing times under air atmosphere. The thicknesses of the surface oxide layers were determined by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
3
37
0
1
Order By: Relevance
“…The reason for this is because ceramic materials are held together by ionic and covalent bonds, which tend to fracture before any plastic deformation (Shabalovskaya et al, 2009, additional reference). Several papers reported that pseudoelastic Ni-Ti SMA samples deformed 0.6-3 %, strain developed cracks in the relatively thick protective TiO 2 layer and exposed Nirich phases leading to increased Ni ion release (Undisz et al, 2009;Zhu et al, 2004, additional references). On the other hand, as shown by Kimura and Sohmura (1987, additional reference), a thin oxide layer is preferable to maintain the integrity of the surface layer to sustain the large deformation induced by the shape memory effect.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…The reason for this is because ceramic materials are held together by ionic and covalent bonds, which tend to fracture before any plastic deformation (Shabalovskaya et al, 2009, additional reference). Several papers reported that pseudoelastic Ni-Ti SMA samples deformed 0.6-3 %, strain developed cracks in the relatively thick protective TiO 2 layer and exposed Nirich phases leading to increased Ni ion release (Undisz et al, 2009;Zhu et al, 2004, additional references). On the other hand, as shown by Kimura and Sohmura (1987, additional reference), a thin oxide layer is preferable to maintain the integrity of the surface layer to sustain the large deformation induced by the shape memory effect.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…This Ni enrichment has been observed on thermally oxidized NiTi where Ni 3 Ti has been found at the metal-oxide interface and islands of metallic Ni have been found in the TiO 2 passive film [38,42] and on wires with very thick oxide [43]. Undisz et al have also observed a concentration of nickel (up to 65 at %) beneath a thermally grown oxide [44].…”
Section: B1 Niti Passive Layermentioning
confidence: 73%
“…Below about 100 C, NiTi remains shiny in air, but at higher temperatures, the oxide surface slowly thickens, giving interference colors [39,44]. A gold color is seen for 30 nm oxide (2-min anneal at 540 C), blue color for 45 nm (5-min anneal at 540 C), turning back to golden after annealing to 30 min (125 nm) [44].…”
Section: B8 Niti High-temperature Oxidationmentioning
confidence: 99%
See 2 more Smart Citations